EFFECT OF WORKPLACE ENVIRONMENT ON JOB SATISFACTION AND PERFORMANCE OF TEACHERS - Muhammad Nafees Ur Rehman; Dr. Muhammad Naveed Jabbar; Naila Fazal Kareem (International Journal of Contemporary Issues in Social Sciences, 2024)
The workplace environment plays a vital role for the development of whole organizations. The major objective of this research was to investigate the effect of the workplace environment on job satisfaction and performance of the academic faculty. The population of the study was public secondary school teachers from Gujranwala whereas, 319 respondents were selected as sample of this study through simple random sampling technique. The study was quantitative based on the correlational research design therefore, self-administered questionnaires were administered to collect the primary data from the respondents through survey method. The Statistical Package for Social Sciences (SPSS) was administered to analyze the research questions. The findings of the study show that there was a positive and significant correlation of workplace environment with job satisfaction and performance. Moreover, there was a positive and moderate effect of the workplace environment on job satisfaction and performance of secondary school teachers. Additionally, Workplace environment had more significant effect on job satisfaction as compared to performance of the teachers. The study is beneficial for the development of teaching learning process at secondary school level through the adaptation of the various innovative techniques.